4‐1: Invited Paper: Technical Cover Glass Designed for Automotive Infotainment Display. Issue 1 (25th September 2020) - Kang, Casey; Linder, Michael; Layouni, Khaled; Hota, Belma; Lesuffleur, Antoine; Park, Jong-se; Sun, Yawei; West, James
Abstract : Common cover glass for automotive infotainment system is adopted from the consumer electronics or architectural industries. A new technical cover glass is designed with high retained strength to enable passing HIT (Headform Impact Testing) without breakage and economic 3D shape designs. In addition, it has optics treatments (AR, AG, AR/AG) to improve display readability.